2018
DOI: 10.17921/2447-8938.2018v20n2p112-118
|View full text |Cite
|
Sign up to set email alerts
|

Clinpro ™ XT Sealant Adhesion to the Occlusal Surface of Primary Molars: Longitudinal Evaluation

Abstract: The study aims to evaluate the bond strength of sealants on deciduous molars. Clinpro ™ XT, Vitremer ™, Fluroshield and Optibond FL materials were applied to the occlusal surface of 40 deciduous lower molars (n = 5). The teeth were prepared for the micro tensile test, obtaining a specimen in a stick format with a cross-sectional area of 0.8 mm 2 . After 24 hours and 6 months of restorative procedures, the specimens were traversed in universal test machine. The statistical analysis used the tooth as experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…This happens because the complex morphology of the occlusal surface makes it difficult to perform mechanical cleaning and reduces the effects of preventive measures 2 . Therefore, sealants that are capable of providing a physical barrier that prevents the retention of microorganism and food particles in pits and fissure have been introduced as one of many minimally invasive approaches in dentistry 3,4 . Their clinical efficiency has been well documented in the literature and reviews have demonstrated that they are effective for preventing both pits and fissure caries, and for minimizing the progression of non-cavitated occlusal carious lesions 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…This happens because the complex morphology of the occlusal surface makes it difficult to perform mechanical cleaning and reduces the effects of preventive measures 2 . Therefore, sealants that are capable of providing a physical barrier that prevents the retention of microorganism and food particles in pits and fissure have been introduced as one of many minimally invasive approaches in dentistry 3,4 . Their clinical efficiency has been well documented in the literature and reviews have demonstrated that they are effective for preventing both pits and fissure caries, and for minimizing the progression of non-cavitated occlusal carious lesions 5,6 .…”
Section: Introductionmentioning
confidence: 99%